Instituting Competency Based Homoeopathic Education: Concept and Challenges (Homoeopathy for All, 2022)
We are seeing a shift in the needs  and demands of the community  in all spheres-political, social,  educational, etc. All sections are  looking for assured outcomes and  are rewarding individuals and  organizations which deliver what  has been promised. The Digital  world has made this process easy  since data to arrive at decisions  is readily tapped from the net.  Educational organizations, for  instance, have their rankings freely  available.
Keywords: community; instance; Educational organizations